(untitled) (Baghdad Science Journal, 2016)
In this work, novel copolymers of poly(adipic anhydride-co-mannitol) were synthesized by melting condensation polymerization of poly(adipic anhydride) with five percentages of mannitol sugar, 1 to 5 Wt.%. These copolymers were purified and then, characterized by FT-IR, which was proved that the cross-linking reaction was caused by nucleophilic attack of mannitol hydroxyl group to acidic anhydride groups of poly(adipic anhydride) backbone and new ester groups were formed and appeared. Also, modified organic-soluble chitosan, N-maleoyl-chitosan, were synthesized by grafting reaction of chitosan with maleic anhydride in DMF as solvent, and it was also purified and characterized by FT-IR. Biodegradation in vitro of the IPNs of poly(adipic anhydride-co-mannitol)-N-maleoyl chitosan networks were evaluated by hydrolytic degradation studies at three different media (PBS, SIF and SGF) for 18 weeks with 92% as maximum degradation and it was found that minimum weight loss of IPNs was noticeably shown in SIF. In addition, hydrolytic degradation percent was decreased with increasing mannitol proportions.